2016
DOI: 10.4049/jimmunol.1600614
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cell Degranulation Is Accompanied by the Release of a Selective Subset of Extracellular Vesicles That Contain Mast Cell–Specific Proteases

Abstract: Mast cells (MC) are well known for their effector role in allergic disorders; moreover, they are associated with diverse modulatory effects in innate and adaptive immunity. It is largely unclear how MC exert these modulating functions. In this article, we show that IgE-mediated MC degranulation leads to a rapid release of high quantities of extracellular vesicles (EV), comparable to the release of preformed mediators. EV are submicron structures composed of lipid bilayers, proteins, and nucleic acids that are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
67
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 77 publications
(100 reference statements)
3
67
0
Order By: Relevance
“…Extracellular vesicles (EVs), such as exosomes (40-150 nm in diameter) and microvesicles (50-1,000 nm in diameter), are released to some degree by most types of cells including mast cells (10,11), dendritic cells (12,13), natural killer cells (14), intestinal epithelial cells (15), and B lymphocytes (16). They are also released by cancerous cells including those in hematological malignancies (17,18), which may generate a greater number of exosomes than normal cells (19,20).…”
mentioning
confidence: 99%
“…Extracellular vesicles (EVs), such as exosomes (40-150 nm in diameter) and microvesicles (50-1,000 nm in diameter), are released to some degree by most types of cells including mast cells (10,11), dendritic cells (12,13), natural killer cells (14), intestinal epithelial cells (15), and B lymphocytes (16). They are also released by cancerous cells including those in hematological malignancies (17,18), which may generate a greater number of exosomes than normal cells (19,20).…”
mentioning
confidence: 99%
“…The greatest differences of EVs subpopulations between AR patients and HS group were identi ed for platelets, endothelium, mastocytes and eosinophil derived EVs. Indeed, during a proin ammatory stimulus an increased amount of EVs released by both platelets and endothelium has been already identi ed as well as for mastocytes derived EVs, speci cally found in greater concentration during an IgE based immune response, a speci c signature of allergic conditions [67][68][69]. The effects of EVs released by mastocytes was also linked to the maturation of the dendritic cells, critical players and sentinels of the immune system in the nasal mucosa during AR [70,71].…”
Section: Discussionmentioning
confidence: 99%
“…MC-derived EVs contain p-MHC complexes or endocytosisderived antigens and can be released by both activated and resting BM-MCs. The main target of these particles is DCs and other professional APCs (51,80,81). Skokos et al investigated the role of MCs in allo-antigen presentation; the authors observed that ovalbumin was more effectively recognized by T cell if taken up by MCs and then transferred to DCs rather than presented directly by DCs (57).…”
Section: Mast Cell-derived Extracellular Vesiclesmentioning
confidence: 99%